Developmental Dysplasia of the Hip: How Does Social Media Influence Patients and Caregivers Seeking Information? - Ashok Para; Brian Batko; Joseph Ippolito; Gabriel Hanna; Folorunsho Edobor-Osula (Children, 2021)
Developmental dysplasia of the hip (DDH) is a common orthopaedic condition affecting newborns. The rapid and vast adoption of social media has changed how we access medical information. The aim of this study was to deepen the understanding of the impact of social media as a tool used by caregivers. A search was performed on the Facebook (FB), Twitter (TW), and YouTube (YT) platforms. Information was quantitatively assessed by category, and number of posts and users. Comments and posts from the social medial platforms were then qualitatively assessed by using a thematic analysis. 16 Facebook pages and groups, 135 YouTube videos, and 5 Twitter accounts related to DDH were identified across 15 countries. A total of 25,471 comments/tweets were recorded. Across the social media platforms, the most common comments theme was “information sharing” (36.1%). Facebook groups had a significantly greater number of comments that were characterized as “social media as a second opinion” in comparison to YouTube videos (p < 0.001), whereas YouTube videos had significantly fewer comments characterized as “sharing information” in comparison to Facebook groups and Facebook pages (p < 0.0001). Orthopaedic surgeons may utilize caregiver presence on social media as an opportunity to help share accurate information and facilitate informed decision-making.